Kendo: Between “religion” and “nationalism” - Tuckett, Jonathan (Journal for the study of religions and ideologies, 2016)
To date, the study of “religion” and “martial arts” is a lacuna of the field in Religious Studies in which the depth of association has long gone unrecognised. What little study there is, however, suffers from a practitioner’s bias in that those writing on martial arts are also attempting to promote the agenda of their own discipline. This paper attempts a more critical approach to show the study of martial arts can contribute to the ongoing problematisation of “religion” as an analytic category, particularly in its relation to “the secular” and “nationalism”. To do this I will draw on the philosophical phenomenology of Husserl, Sartre and Schutz to argue that “religions”, “nationalisms” and “martial arts” are all names given to modes of naturalisation. By this I mean they are means by which a person “fits” within their life-world and deals with the problems of surviving and thriving.In this case of martial arts, these can be seen as modes of naturalisation through debates on “sportification”. As commonly conceived, the sportification of a martial art risks impeding its “spiritual” aspects. It is the martial artists’ understanding of “spiritual” as something public and serious that mark it out as a mode of naturalisation. In the case of “religion” and “nationalism” these are ideological means of categorising modes of naturalisation, primarily as a means of “Othering”. By looking at the case of Kendo and its origins in the samurai, this paper will show the fluidity with which these ascriptions can be applied to a single “tradition” depending on context.